New technology used in gas turbine blade materials - Estrada M., Carlos A. (Scientia et Technica, 2007)
After the world word II, gas turbines became an important technology for its applications in aeronautics and industrial processes. At the beginning materials used for the engine’s construction and more precisely; materials used in compressor and turbine blade-materials, could not survive more than a few hundred hours at then relatively modest temperatures and low power settings; on the other hand, reliability and thermodynamic efficiency were relatively low, producing some accidents causing damage to equipment and injures to people. In this paper, new technologies for increasing the performance, reliability and emissions in gas turbines due improvements materials, are discussed and presented.